2015
DOI: 10.1002/star.201400258
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and characterization of a novel GH13 saccharifying α‐amylase AmyC from Corallococcus sp. EGB

Abstract: A novel amylase AmyC gene (amyC) from Corallococcus sp. EGB was cloned and expressed in Esherichia coli. Analysis of the sequence homology showed that AmyC shared 92% identity with the putative a-amylase from Corallococcus coralloides DSM 2259 and formed a separate branch from other amylases. The recombinant AmyC (rAmyC) was purified and biochemically characterized. rAmyC hydrolyzes various starch and maltooligosaccharides larger than G4 to glucose to maltotetraose without production of other oligosaccharides,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…strain EGB. We isolated and characterized a novel liquefying maltohexaose-forming ␣-amylase (AmyM) and saccharifying ␣-amylase (AmyC) from the EGB strain (26,27). We assumed that AmyM is the main extracellular liquefying amylase for utilizing starch in Corallococcus sp.…”
Section: Resultsmentioning
confidence: 99%
“…strain EGB. We isolated and characterized a novel liquefying maltohexaose-forming ␣-amylase (AmyM) and saccharifying ␣-amylase (AmyC) from the EGB strain (26,27). We assumed that AmyM is the main extracellular liquefying amylase for utilizing starch in Corallococcus sp.…”
Section: Resultsmentioning
confidence: 99%
“…Bacteriolytic myxobacteria can utilize several polysaccharides and maltotriose as carbon source, but mono-or disaccharides do not stimulate growth [45]. Several new glycoside hydrolases from Corallococcus species, including some from family GH13, have already been characterised in the past few years [46][47][48][49][50][51]. Those GH13 hydrolases indeed process maltooligosaccharides, but the GH13 phosphorylase discussed in this work did not appear to show such activity.…”
Section: Discussionmentioning
confidence: 68%
“…Except that, Wu et al (2015) reported the amylase AmyC from Corallococcus sp. EGB showed the highest hydrolytic activity on potato starch, and its activity was 21% higher than that on soluble starch (23).…”
Section: Substrate Speci City Of Amyflamentioning
confidence: 99%
“…Except that, Wu et al (2015) reported the amylase AmyC from Corallococcus sp. EGB showed the highest hydrolytic activity on potato starch, and its activity was 21% higher than that on soluble starch (23). Similar results were found in the α-amylase RoAmy of Rhizopus oryzae, RoAmy exhibited the highest activity on wheat starch and corn starch, which was about 30% higher than that on soluble starch (24).…”
Section: Substrate Speci City Of Amyflamentioning
confidence: 99%